Sustainable Industrial Development in Punjab, Pakistan - World Bank Group (World Bank, Washington, DC, 2019)
Greening Pakistan’s industry has become an imperative to minimize its adverse impacts on the environment and society, but also to sustain the sector’s growth. Despite substantial growth in recent decades, the industrial sector is yet to make its full contribution to Pakistan’s development. Limited consideration of the growing resource use, waste, and pollution that have accompanied industrialization has imposed mounting economic, environmental, and social costs. This is particularly true in large urban centers around which industries agglomerate, such as Lahore and Karachi. At the same time, poor environmental management has become a liability for Pakistan’s industries, which notably undermines the competitiveness of export-oriented manufacturing sectors. The challenges posed by industries’ lack of environmental sustainability jeopardize Pakistan’s development and are expected to worsen under a business-as-usual scenario. The Government of Punjab (GoPunjab) should put sustainable industrialization at the center of its growth strategy and should modernize its policy toolkit for this purpose. Punjab’s Growth Strategy 2018 envisioned that growth must be private sector-led, investment-driven, export-oriented, environmentally sound, and employment-intensive. Developing an ambitious and integrated policy to green industries would be a strategic way to jointly achieve these objectives, and in so doing, Punjab could become a lighthouse for the rest of Pakistan. This would require both strengthening environmental policy (stick) and developing elements of a green industrial policy looking at investment, innovation, and trade (carrot). Importantly, policy objectives should go beyond the current focus on pollution control and compliance, to include preventive and circular approaches at the firm and industry levels that could yield environmental and productivity/competitiveness gains. The time has come to integrate these approaches in strategies and regulations, and to institutionalize and mainstream them across relevant government agencies.